A combination effect of manual assisted cough techniques and respiratory proprioceptive neuromuscular facilitation on ventilatory decompression craniotomy patients: a case report - Akshay Kumar, Namathota Chandra; Kamble, Karuna (International Journal of Research in Medical Sciences, 2023)
After traumatic brain injury (TBI), brain starts swelling due to the formation of hematomas in the intracranial cavity and owing to forming rigid nature of the skull. Decompression craniotomy is a surgical procedure in which skull is removed and underlying dura is opened-for escalating the brain edema. Patients with TBI will be on prolonging bed rest depending on severity of injury and level of consciousness i.e., low GCS score and neuromuscular weakness. Prolong bed rest can contribute to cardio-pulmonary dysfunction and there by receiving ventilatory support via endotracheal tube or tracheostomy. Experience of ineffective cough reduced airway in the lung field due to impaired respiratory muscle weakness or paralysis which contributes various pathophysiological effects in TBI. A case report study of 51 years old patient diagnosed with TBI with left sided subdural haemorrhage with right extradural haemorrhage who operated for decompression craniotomy and with ventilatory support. Outcomes were taken on day one and fourteenth day i.e., vitals, GCS score, RLA stage, chest expansion, lung compliance and ICP, there is significant improvements in outcomes is seen after intervention. In the present case study, combination of manual assisted cough techniques (MACT) and respiratory PNF have shown improvement in efficacy of cough, thoracic cage mobility and weaning off from ventilator, hence by implementing these combination techniques, will reduce ICU stay and improve quality of life.